(untitled) (Quinto Sol, 2022)
To address the theme of religion in the Constitutions of Santiago del Estero, it must be borne in mind that Santiago del Estero is an Argentine province with a centralized government in the form of strong governors, with deep-rooted family ties and clientelistic networks, as well as a strong Catholic tradition, often used by the governments themselves to consolidate their hold on power. However, they did not always manage to impose their religious ideas on constitutional reforms, due to opposition from secularist sectors or even the ecclesiastical hierarchy itself. In the long term, the constitutional process in Santiago del Estero shows continuities and ruptures, from the first constitution in the mid-19th century to the last one at the beginning of the 21st century, as well as variations according to the governments in power and the ecclesiastical authorities at each moment, although some of society’s demands were also evident, with different positions.